Solidarity and fairness in times of crisis - Cappelen, Alexander W.; Falch, Ranveig; Sørensen, Erik Ø.; Tungodden, Bertil (Journal of economic behavior & organization, 2021)
•Experiment with more than 8000 Americans on how the pandemic changes moral views.•Identifies causal mechanism by making the pandemic salient for treated respondents.•The pandemic makes people more willing to prioritize society’s problems.•The pandemic makes people more tolerant of inequalities due to luck.•The pandemic may change long-term political attitudes. In a large-scale pre-registered survey experiment with a representative sample of more than 8000 Americans, we examine how a reminder of the COVID-19 pandemic causally affects people’s views on solidarity and fairness. We randomly manipulate whether respondents are asked general questions about the crisis before answering moral questions. By making the pandemic particularly salient for treated respondents, we provide causal evidence on how the crisis may change moral views. We find that a reminder about the crisis makes respondents more willing to prioritize society’s problems over their own problems, but also more tolerant of inequalities due to luck. We show that people’s moral views are strongly associated with their policy preferences for redistribution. The findings show that the pandemic may alter moral views and political attitudes in the United States and, consequently, the support for redistribution and welfare policies.